CONCEPTS OF RELIGION IN MODERN AMERICAN RAP LYRICS - Riazanov, I.; Yakuba, V. (Studia Philologica, 2020)
The article studies verbalization mean of religious concepts in Kendrick Lamar’s songs of his 2017 album DAMN. After introducing the inventory of lexemes representing themes of religion, the authors argue for correlations with basic concepts and explain the structure of the thematic field, representing religion in all fourteen songs of the album. The album structure and each song of it include over a hundred tokens referring to various religious concepts – mainly GOD, SIN, and PRAY, each of them being verbalized by a group of lexemes, fifteen total, which share certain semantic components. The micro-contexts with biblical quotes will be regarded as convergence points of the album’s text and analyzed individually for their stylistic value, but in general contributing to the general view of the album as a spiritual challenge. Through each next song a new aspect of religious concepts adds to the existing inventory, certain repetitions and cross-contextual allusions confirm and support them, adding coherence and continuity to the album’s structure. Out of fourteen songs of the album seven directly verbalize basic religious concepts through the notions of God, pride, humility, lust, love, loyalty, fear. This explicit structural feature together with the ambiguous title offer a series of logical steps in evaluating the sinful vs virtuous choices. This contrast is identified and sustained through such stylistic devices as repetitions, allusions, rhetorical questions and others. Key words: religious concept, song lyrics, verbalization, American rap, coherence, stylistic value.